553 CUE-100 series Immuno-STATs from concept to the clinic: Leveraging protein engineering to stimulate and selectively deliver affinity-attenuated IL-2 to antigen-specific T cells. (9th November 2020) - Histed, Alex; Girgis, Natasha; Moreta, Miguel; Soriano, Jonathan; Luke Witt, BS; Merazga, Zohra; Diaz, Fulvio; Zhao, Fan; Kemp, Melissa; Ruthardt, Paige; Thapa, Dharma; Suri, Anish; et al.
Abstract : Background: Activation of T cells requires a specific peptide/HLA (human leukocyte antigen) signal presented by an interacting immune or target cell along with engagement of co-stimulatory molecules or cytokine receptors. Cue Biopharma has developed a proprietary biologics platform, termed Immuno-STAT™ (Selective Targeting and Alteration of T cells), wherein a singular protein framework incorporates peptide/HLA complexes and co-stimulatory or cytokine signals. The CUE-100 series Immuno-STATs selectively deliver rationally engineered IL-2 molecules to antigen-specific T cells. The IL-2 molecules in the CUE-100 series Immuno-STATs contain mutations that attenuate binding to IL-2 receptors alpha and beta, which minimizes activation of regulatory T cells (Tregs) and the irrelevant non-antigen-specific T cell repertoire. We have demonstrated that CUE-100 series Immuno-STATs specific for different antigenic peptides (from HPV16, WT1, MART-1, CMV, Flu, and HIV) induce expansion of functional, oligoclonal, antigen-specific repertoires from human PBMCs. The lead clinical candidate CUE-101, presenting the E711-20 peptide from HPV-16 in the context of HLA-A*02:01, is currently being tested in a Phase 1 clinical trial in recurrent/metastatic head and neck cancer patients with evidence of dose-proportional PK, early pharmacodynamic effects and signals of clinical activity. Methods: CUE-100 series Immuno-STATs were tested with human PBMCs to demonstrate specific T cell activation and expansion. Expanded T cell clonality was assessed by single cell TCR sequencing. Responses of T cells to peptide-presenting targets was evaluated by cytokine staining and by assessing their ability to kill target cells. In vivo activity of CUE-100 series Immuno-STATs was assessed in HLA-A2 transgenic mice. Results: Data demonstrate that the CUE-100 series Immuno-STATs selectively activate antigen-specific CD8+ T cells. Signaling, cell-based assays and cytokine release studies confirmed functional attenuation of the IL-2 components of the CUE-100 series, which allows for a favorable safety and selectivity profile. Immuno-STATs demonstrated robust expansion of CD8+ T cells after primary stimulation of unprimed hPBMCs, or re-stimulation of hPBMCs after initial cognate peptide stimulation. In addition, CUE-100 series Immuno-STATs expanded CD8+ T cells in naïve HLA-A*02 transgenic mice. In both cases the expanded T cells exhibited a polyfunctional response upon challenge with peptide-presenting target cells. Conclusions: The presented data suggests that CUE-100 series Immuno-STATs have the potential to enhance anti-tumor immune responses by inducing a robust antigen-specific, oligoclonal, polyfunctional T cell repertoire. Early validation of CUE-100 series Immuno-STATs is obtained through the emerging signs of pharmacodynamic and clinical activity in the ongoing Phase I trial with CUE-101. Reference: Quayle SN, Girgis N, Thapa DR, et al. CUE-101, a Novel HPV16 E7-pHLA-IL-2-Fc Fusion protein, enhances tumor antigen specific T cell activation for the treatment of HPV16-driven malignancies. Clin Cancer Res 2020;26:1953–64.